Evaluation of reference genes for RT‐qPCR gene expression analysis in Arabidopsis thaliana exposed to elevated temperatures. (6th January 2022) - Škiljaica, A.; Jagić, M.; Vuk, T.; Leljak Levanić, D.; Bauer, N.; Markulin, L.
ABSTRACT: Increases in environmental temperature are directly linked to the issue of climate change and are known to significantly disrupt plant growth and development. Studies of gene expression in plants commonly include RT‐qPCR but the reliability of the method depends on the use of suitable reference genes for data normalization. Despite this, no reference genes have been validated specifically for experiments in Arabidopsis thaliana employing treatments with elevated temperature. Here, ten genes were selected for expression stability analysis based on the screening of available literature and microarray data from temperature‐treated A. thaliana . Expression levels of candidate reference genes were measured in 12‐day‐old seedlings, rosette leaves and flower buds of 5‐week‐old A. thaliana plants exposed to five different temperatures (22°C, 27°C, 32°C, 37°C and 42°C) and their expression stabilities were assessed using four statistical algorithms (BestKeeper, geNorm, NormFinder and comparative ΔCq method). This study provides reliable reference genes for use in A. thaliana RT‐qPCR expression analyses employing elevated temperature treatments, namely OGIO and PUX7 in seedlings, UBC21 and PUX7 in leaves, TIP41 and UBC21 in buds, and TIP41 and UBC21 in all three tissues combined. Orthologues of these genes can be of potential use in less studied plants, especially agricultural species heavily affected by climate change. Abstract : Microarray data offers a rich source of candidate reference genes for RT‐qPCR data normalization, and here several were validated for use in experiments on A. thaliana employing elevated temperatures.